Investigação de genes de resistência a carbapenêmicos, cefalosporinas e quinolonas e tipagem molecular de Enterobacter spp isolados de pacientes internados em um hospital terciário do Estado de São Paulo - Martins, Evelin Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Enterobacter genus comprises facultative anaerobic bacteria, glucose fermenters and ubiquitous in nature. Currently, there are 25 species of Enterobacter spp and two which can be identified by biochemical, molecular methods or by mass spectrometry. Infections caused by Enterobacter spp are skin and soft tissues, bacteremia and pneumonia, and for the treatment of these, the most commonly used antimicrobials are carbapenems, cephalosporins and quinolones. However, antimicrobial resistance has increased the Enterobacter spp mainly due to enzymatic mechanisms encoded by plasmid genes. The objectives of this study were to evaluate the antimicrobial susceptibility profile, investigate beta-lactamase genes (blaTEM-like, blaSHV-like, blaVEB-like, blaPER-like, blaGES-like, blaCTX-M-like), carbapenemases (blaKPC, blaIMP, blaVIM, blaNDM, blaGES and blaOXA-48) and enzymes that confer resistance to quinolones (qnrA, qnrB, qnrS, aac (6') - Ib-cr and qepA) and determine the genetic similarity among isolates of Enterobacter spp. Sixty isolates of Enterobacter spp resistant to carbapenems, cephalosporins ( third and fourth generation) and quinolones from patients admitted to the Base Hospital (HB), were send Laboratory - Microorganisms Research Centre the School of Medicine of São José do Rio Preto (FAMERP), where DNA extraction, the investigation of genes and molecular typing by ERIC-PCR were carried out. The blaKPC resistance gene was detected in 22% of the isolates. The genes blaTEM-like and blaCTX-M-like 82%, blaSHV-like 3% of the isolates. The group 1 CTX-M was detected in 56.5%, of group 2 in 41.3% and 8/25 group at 2.2% of the isolates. The quinolone resistance genes qnrA, qnrB, and qnrS were detected in 40% 22% 2% of the isolates, respectively. The ERIC-PCR typing by genetic generated twelve groups (G1 to G12) for E. cloacae and one group (G1) for E. aerogenes, horizontal transfer of resistance genes in some groups was observed, but the ...

O gênero Enterobacter compreende bactérias anaeróbias facultativas, fermentadores de glicose e ubíquo na natureza. Atualmente, existem 28 espécies de Enterobacter spp que podem ser identificadas por métodos bioquímicos, moleculares ou por espectrometria de massa. As infecções mais causadas por Enterobacter spp são de pele e tecidos moles, pneumonias e bacteremias, e, para o tratamento destas, os antimicrobianos mais utilizados são carbapênemicos, cefalosporinas e quinolonas. Entretanto, a resistência aos antimicrobianos tem aumentado no gênero Enterobacter, principalmente, devido à mecanismos enzimáticos codificados por genes plasmidiais. Os objetivos deste estudo foram avaliar o perfil de susceptibilidade aos antimicrobianos, investigar genes de beta-lactamases (blaTEM-like, blaSHVlike, blaVEB-like, blaPER-like, blaGES-like, blaCTX-M-like), carbapenemases (blaKPC, blaIMP, blaVIM, blaNDM, blaGES e blaOXA-48) e de enzimas que conferem resistência as quinolonas (qnrA, qnrB, qnrS, -Ib-cr e qepA) e determinar a similaridade genética entre os isolados de Enterobacter spp. Sessenta isolados de Enterobacter spp resistentes aos carbapenêmicos, cefalosporinas de terceira e quarta geração e quinolonas provenientes de pacientes admitidos em diferentes unidades de internação do Hospital de Base de São José do Rio Preto (HB) foram encaminhados ao laboratório CIM-Centro de Investigação de Microrganismos da Faculdade de Medicina de São José do Rio Preto (FAMERP), onde foram realizadas a extração de DNA, a investigação dos genes por PCR e a tipagem molecular por ERIC-PCR. O gene de resistência blaKPC foi detectado em 22% dos isolados. Os genes blaTEM-like e blaCTX-Mlike em 82% e blaSHV-like em 3% dos isolados respectivamente. O grupo 1 de CTX-M foi detectado em 56,5%, do grupo 2 em 41,3% e do grupo 8/25 em 2,2% dos isolados. Os genes de resistência a quinolonas detectados foram qnrA, qnrB e qnrS em 40%, 22% 2% dos isolados...
Keywords: Microbiologia médica; Anti-infecciosos; Enterobacterias; Drogas - Resistência em microorganismos; Antibioticos beta-lactamicos; Tipagem molecular; Infeccão hospitalar - São José do Rio Preto (SP); Medical microbiology